ZELA, ACCLAMATIONS, CARACALLA – AND PARTHIA?. (23rd June 2016) - BURNETT, ANDREW
Abstract: A coin which has lain unrecognized in the BM, which can be identified as an unpublished coin of Zela, proclaims that if 'the emperors are victorious the world is happy'. The formula is analysed in the context of imperial acclamations and their language, which differs from that normally found on coinage. It is suggested that the coin may have been struck in connection with an otherwise unknown visit by Caracalla to the East in AD 207, for which other evidence is assembled. A catalogue of acclamations on Roman coins, medallions, and tokens is provided.